2011
DOI: 10.2478/s11534-011-0073-9
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical forecast of the hydrogen bond changes in the electronic excited state for BN and its derivatives

Abstract: Ê Ú ¼ ÖÙ ÖÝ ¾¼½½ ÔØ ¼ Ù Ù×Ø ¾¼½½ ×ØÖ ØThe relationship between electronic spectral shifts and hydrogen-bonding dynamics in electronically excited states of the hydrogen-bonded complex is put forward. Hydrogen bond strengthening will induce a redshift of the corresponding electronic spectra, while hydrogen bond weakening will cause a blueshift. Time-dependent density function theory (TDDFT) was used to study the excitation energies in both singlet and triplet electronically excited states of Benzonitrile (BN), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…These first findings by Zhao et al paved the way for numerous other theoretical and experimental studies to understand how the electronic properties of different chromophores are modified when H-bonding interactions are involved [3,25,37,94,95]. For example, Wang et al theoretically investigated the low-lying electronic excited states of the benzonitrile (BN) molecule and its derivatives as hydrogen bond acceptors in a hydrogen-donating MeOH solvent [3]. Additionally, the spectral features of fluorenone (FN) molecules in MeOH (Figure 1e) could be explained by a change in the strength of the intermolecular H-bond between FN and solvent molecules upon photoexcitation [37].…”
Section: Shift Of Electronic Spectral Peaks In Protic Solventsmentioning
confidence: 99%
See 3 more Smart Citations
“…These first findings by Zhao et al paved the way for numerous other theoretical and experimental studies to understand how the electronic properties of different chromophores are modified when H-bonding interactions are involved [3,25,37,94,95]. For example, Wang et al theoretically investigated the low-lying electronic excited states of the benzonitrile (BN) molecule and its derivatives as hydrogen bond acceptors in a hydrogen-donating MeOH solvent [3]. Additionally, the spectral features of fluorenone (FN) molecules in MeOH (Figure 1e) could be explained by a change in the strength of the intermolecular H-bond between FN and solvent molecules upon photoexcitation [37].…”
Section: Shift Of Electronic Spectral Peaks In Protic Solventsmentioning
confidence: 99%
“…This led to the conclusion that, in this case, the intermolecular H-bond should be weakened in the T 1 and S 1 states and strengthened in the S 2 state. These first findings by Zhao et al paved the way for numerous other theoretical and experimental studies to understand how the electronic properties of different chromophores are modified when H-bonding interactions are involved [3,25,37,94,95]. For example, Wang et al theoretically investigated the low-lying electronic excited states of the benzonitrile (BN) molecule and its derivatives as hydrogen bond acceptors in a hydrogen-donating MeOH solvent [3].…”
Section: Shift Of Electronic Spectral Peaks In Protic Solventsmentioning
confidence: 99%
See 2 more Smart Citations
“…What's more, it has been demonstrated that both the excited-state hydrogen bond strengthening and weakening play very significant roles in the processes of internal conversion (IC) [13], electronic spectral shifts (ESS) [12], photoinduced electron transfer (PET) [14], intramolecular charge transfer (ICT) [15,16], and metal-to-ligand charge transfer (MLCT) [17,18], and so on. It is important to mention that an effective rule, illustrating and inferring excited-state hydrogen bonding strengthening or weakening via an electronic spectral red-shift or blue-shift, have been presented recently [12,19], and the effective rule has been taken into account to explain the experiment by other groups [20][21][22][23][24][25][26]. A great deal of the studies have been focused on the hydrogen bonding dynamics, however, it is still desirable to carry out further works dealing with the effect of the excited-state hydrogen bonding dynamics on the photochemistry, photophysics and photobiology.…”
Section: Introductionmentioning
confidence: 99%